2022
DOI: 10.18844/wjet.v14i1.6642
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ICT integration on the development of vocational high school teacher TPACK in the digital age 4.0.

Abstract: To investigate the impact of the integration of information and communication technology (ICT) on the development of the Technological Pedagogical Content Knowledge (TPACK) framework for Vocational High School teachers in the Digital Era 4.0, this research will look at the integration of ICT. The evaluation of the Online Learning Implementation Plan (RPP) of the Computer and Network Engineering Department in the even semester of the 2020/2021 academic year revealed the impact of ICT on instructors' TPACK. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…When the qualitative and quantitative findings are combined and interpreted together, it is seen that teachers believe that using information and communication technologies in education has the most important positive effects on entertaining and motivating aspects. Similar to the results obtained in this study, many studies in the literature concluded that teachers have positive views toward using ICT in education (Becker, 2001;Carnoy, 2004;Eng, 2005;Fernández-Gutiérrez, Gimenez & Calero, 2020;Gök, Turan & Oyman, 2011;Gömleksiz & Pullu, 2017;Istiningsih, 2022;Livingstone, 2012;Milliken & Barnes, 2002;Olaore, 2014;Voogt et al, 2013).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 88%
“…When the qualitative and quantitative findings are combined and interpreted together, it is seen that teachers believe that using information and communication technologies in education has the most important positive effects on entertaining and motivating aspects. Similar to the results obtained in this study, many studies in the literature concluded that teachers have positive views toward using ICT in education (Becker, 2001;Carnoy, 2004;Eng, 2005;Fernández-Gutiérrez, Gimenez & Calero, 2020;Gök, Turan & Oyman, 2011;Gömleksiz & Pullu, 2017;Istiningsih, 2022;Livingstone, 2012;Milliken & Barnes, 2002;Olaore, 2014;Voogt et al, 2013).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 88%
“…TCK, skills and knowledge of digital technology and knowledge of the field of study or learning materials; TPK, skills and knowledge of digital technology and knowledge of learning processes and strategies; and TPCK, skills and knowledge of digital technology, knowledge of learning processes and strategies and knowledge of the field of study or learning materials. Istiningsih (2020) stated that by training TPACK to teachers, it will have a positive impact on teachers, namely teachers are able to solve problems that arise during online learning activities, provide authentic assessments in learning, improve teacher skills can using technology in the 21st century, where the use of TPACK has nothing to do with gender differences (Cahyani et al, 2021;Istiningsih, 2022;Septiyanti, et al, 2020;Tashbolatovna et al, 2022). This finding is also supported by several research results, namely science teachers have a skill level in applying TPACK in teaching science, improving the quality of teaching in the classroom, increasing HOTs, increasing scientific literacy students, creating an effective, fun, interesting and creative learning environment (Dais et al, 2020;Dinara et al, 2022;Ella, 2019;Hartati et al, 2019;Joseline et al, 2021;Leni et al, 2021;Sarjoni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Students who are close to the problems of the community will not feel alienated from the environment and they will be able to contribute to problem-solving. This thought is also highly relevant to the characteristics of TPACK, one of which is the material must be authentic (Istiningsih, 2022). ( 2) Students need to respond to the development of online (contemporary) literary media not just printed literature.…”
Section: Social Media Toolsmentioning
confidence: 99%
“…Students who are familiar with social media use it as a learning resource or a form of technological and social adaptation amid the panic caused by the COVID-19 pandemic. This information technology adaptation is of high importance for students to support their learning success (Shulga et al, 2021) and to educate students to be strong people in the field of technology and pedagogy with TPACK principles (Istiningsih, 2022). Moreover, online learning has provided benefits to students, such as a sense of comfort, responsibility, respect for others and awareness of values (Meruyert, 2022).…”
Section: Social Media Toolsmentioning
confidence: 99%
See 1 more Smart Citation